Textural analysis and plagioclase grain size distribution of the Rooiberg Group, Bushveld Igneous Complex, South Africa - Roberts, R.J. (James) (University of Pretoria, 2024)
Dissertation (MSc (Geology))--University of Pretoria, 2024.